Adaptation of the VegSyst model to outdoor conditions for leafy vegetables and processing tomato. (May 2019) - Giménez, C.; Thompson, R.B.; Prieto, M.H.; Suárez-Rey, E.; Padilla, F.M.; Gallardo, M.
Abstract: The VegSyst model, initially developed for nitrogen (N) and irrigation recommendations for greenhouse-grown vegetable crops, was adapted for outdoor conditions, for lettuce, spinach and processing tomato. The major change introduced into the existing VegSyst model was to include evaporative demand, as transpiration use efficiency (TUE), as an additional determinant of dry matter production (DMP); PAR radiation being the other determinant. For daily simulation of DMP, VegSyst-Outdoors selects the smallest of the two DMP values calculated using both approaches. Data from studies conducted in different locations and years were used for calibration and validation. For lettuce, data from crops grown in California and Spain were used, for three lettuce types – Crisphead, Romaine and Batavia. One crop of each lettuce type was used for calibration. Different crops of Crisphead and Batavia lettuce were used for validation; no data were available for validation of Romaine lettuce. For spinach, calibration was conducted with data from a winter-grown crop grown in Spain, and validation was done with data from a spring-grown crop in Spain from a different region and year. For processing tomato, the calibration crop was grown in Spain, and validation was conducted with data from 10 different crops from California, Italy and Spain, and from different years. Radiation-use efficiency (RUE) values ranged from 2.1 to 2.8 g MJ −1 PAR for the three lettuce types, and were 2.2 and 2.3 g MJ −1 PAR for spinach and processing tomato, respectively. TUE was different among lettuce types, being 3.8 g kg −1 for Crisphead, 5.0 g kg −1 for Romaine, and 5.4 g kg −1 for Batavia. TUE values for spinach and processing tomato were 5.0 and 5.6 g kg −1, respectively. Following adaptation to outdoor conditions, crop DMP, crop N uptake and crop evapotranspiration (ETc) were accurately simulated in most of the validation crops. The diversity of sites and years of the crops examined demonstrated the robustness of the VegSyst model when adapted to outdoor conditions. Highlights: The VegSyst model for greenhouse crops was adapted for outdoor conditions. Daily dry matter production (DMP) based on either TUE or RUE. Adapted model calibrated and validated for lettuce, spinach and processing tomato. DMP, N uptake and ETc accurately simulated in most validation crops. Diversity of validation crops demonstrated robustness of adapted model.